Potential benefits of phenolic compounds extracted from winemaking wastes - Baffi, Milla Alves; Vanzela, Ellen Silva Lago [UNESP]; Gomes, Eleni [UNESP]; Da-Silva, Roberto [UNESP] (My University, 2014)
The grape is one of the most popular fruit crops in the world and the winemaking sector produces large amounts of under-utilized by-products (pomace), which have significant economic potential. Grape pomace (consisting mainly of skins, seeds and stems) has been evaluated as a promising source of antioxidants because of its high content of phenolic compounds (gallic acid, flavan-3-ols, flavonoids, stilbene and anthocyanins). In addition, studies have demonstrated some of the biological effects of these phenolic compounds such as anti-carcinogenic, anti-mutagenic and antimicrobial activity. As a result, there is a considerable interest in alternative approaches for the control of infections and preservation of foods using biologically active phenolic compounds extracted from winemaking wastes. However, the chemical composition and availability of these compounds in grape pomace depends on various factors: grape varieties, the contact time between the skins and the wine in fermentation and, also, environmental factors. Moreover, the yield of phenolic compounds extracted from these residues can vary from 4.0 to 65.0% depending on the extraction conditions (extraction solvent, extraction time), grape variety and grape fraction. Therefore, the recovery of these substances from this residue of the wine industry, with their potential application, could represent a significant advance in maintaining environmental balance, as well as adding value to the byproducts of winemaking. For all the mentioned reasons, the present chapter describes the importance of the recycling of grape pomace as a prospective source of phenolic compounds with application in the food and pharmaceutical industries and with potential benefits to human health.
Keywords: Antimicrobial activity; Phenolic compounds; Winemaking residues